Verification Test of the Low Complexity Enhancement Video Coding (LCEVC) Standard - Battista, Stefano; Meardi, Guido; Ferrara, Simone; Ciccarelli, Lorenzo; Maurer, Florian; Conti, Massimo; Orcioni, Simone (IEEE transactions on circuits and systems for video technology, 2023)
This paper reports the methodology and results of the test campaign performed in the context of the development of the Low Complexity Enhancement Video Coding (LCEVC) ISO standard. LCEVC is a video coding technology that can be applied in conjunction to any other single-layer video coding technology to re-encode the residuals between the original video and its compressed representation. The first part of the paper describes the methodology for the verification tests: Requirements, Test Conditions, Test Sequences, Test Methods (Metrics); the second one reports the results of the objective and subjective tests carried out applying such methodology. The bitrate savings achieved with LCEVC when used in conjunction with four video codecs (AVC, HEVC, EVC, VVC) are reported.